The Use Of Agricultural Lands In Northern Moldova Plateau - Capcelea Victor; Sofroni Valentin (Present Environment and Sustainable Development, 2015)
This article comprises a study on the development and use of agricultural lands in Northern Moldova Plateau. The spatial aspects of using these categories of lands within the limits of study region are also described. In this article, the research findings are reflected on the basis of presented data by Agency for Land Relations and Cadastre of the Republic of Moldova. Scientific publication also describes some current issues on agricultural lands use in Northern Moldova Plateau.